Polyarteritis associated with Yersinia enterocolitica infection. - Pile, K (1992)
A patient developed polyarteritis, predominantly affecting the muscles, 10 days after a Yersinia enterocolitica O:3 infection. Immunoperoxidase staining showed Yersinia enterocolitica O:3 antigen in the subendothelial layer of the blood vessels. This suggests that vasculitis should be considered as a rare manifestation of Yersinia enterocolitica infection.